Pengaruh Orientasi Sudut Terhadap Faktor Delaminasi dan Nilai Kekuatan Tarik Pada Proses Pengeboran Komposit Fiberglass woven bermatriks Poliester - Paundra, Fajar; Pujiyulianto, Eko; Muhyi, Abdul; Sri Bagaskara, Firman; Manzeis, Ilhan; Ramadhan Siregar, Ilham; Elmiawan, Puguh (Infotekmesin, 2024)
Composite is a material that is formed from a combination of 2 or more materials. The orientation of the inclination angle of the webbing on the composite affects the tensile strength value. This research was conducted to determine the effect of variations in the angle of inclination of the webbing and the phenomenon of delamination on the value of tensile strength. The process of making fiberglass woven fiber composites and a mixture of resin and catalyst uses the vacuum bagging method. The variations used in this study are the angle of inclination of the webbing 0°, 15°, 30° and 45°. Tensile test specimens using the ASTM D638 standard. The specimens that have been cut will then be perforated with a diameter of 4 mm using a milling machine. Tensile testing was carried out using a Universal Testing Machine. The highest tensile strength value is at an angle of 0° with a value of 189.30 MPa and the lowest tensile strength is at an angle of 45° with a value of 34.25 MPa and for the value of the delamination factor has little effect on the value of tensile strength.